Exploring 2SLGBTQ+ University Students' Experiences with Mental Health and Accessing Formal and Informal Sources of Mental Health Support - Gilmour, Meggie (Université d'Ottawa / University of Ottawa, 2025)
Background: 2SLGBTQ+ (Two-Spirit, Lesbian, Gay, Bisexual, Transgender, Queer/Questioning, +) university students are at a higher risk for mental health issues and an increased need for mental health support than non-2SLGBTQ+ university students, yet their experiences with mental health and accessing formal and informal sources of mental health support remain underexplored. Methods: Semi-structured interviews were conducted with sixteen 2SLGBTQ+ students from two universities in a large city in Ontario. Participants shared their mental health experiences and elaborated on access to support, focusing on challenges encountered and strategies implemented before and during university. They also provided suggestions for improving these experiences. These interviews were audio-recorded and transcribed. The transcripts were coded using NVivo and analyzed using Braun & Clarke's (2006) six-step thematic analysis process, grounded in an interpretative approach. Results: Participants described challenges related to harmful external perceptions, internalizing harmful perceptions, insufficient representation and resources, and educating others. They illustrated strategies such as moving to a different social environment, unlearning and discovering, assessing individuals and social environments, and supporting others. Participants also shared suggestions for improvements at individual, organizational, and system levels. Conclusion: This study offers in-depth insights into 2SLGBTQ+ university students' mental health experiences with mental health and access to formal and informal sources of support. This study also provides useful information for consideration by university and mental health policy makers, service providers and others who interact with 2SLGBTQ+ individuals for ameliorating their experiences.
Keywords: 2SLGBTQ+ University Students; Mental Health; Qualitative Research; Lived Experience; Formal and Informal Sources of Support; Interviews; Youth